Complications and Survival After Long Posterior Instrumentation of Cervical and Cervicothoracic Fractures Related to Ankylosing Spondylitis or Diffuse Idiopathic Skeletal Hyperostosis. Issue 4 (15th February 2015) - Robinson, Yohan; Robinson, Anna-Lena; Olerud, Claes
<x xml:space="preserve">Abstract</x> Study Design. Prospective cohort study. Objective. This study investigates the results of long posterior instrumentation with regard to complications and survival. Summary of Background Data. Fractures of the cervical spine and the cervicothoracic junction related to ankylosing spinal disease (ASD) endanger both sagittal profile and spinal cord. Both anterior and posterior stabilization methods are well established, and clear treatment guidelines are missing. Methods. Forty-one consecutive patients with fractures of the cervicothoracic junction related to ASD were treated by posterior instrumentation. All patients were followed prospectively for 2 years using a standardized protocol. Results. Five patients experienced postoperative infections, 3 patients experienced postoperative pneumonia, 2 patients required postoperative tracheostomy, and 1 patient had postoperative cerebrospinal fluid leakage due to accidental durotomy. No patient required reoperation due to implant failure or nonunion. Mean survival was 52 months (95% confidence interval: 42–62 mo). Survival was affected by patient age, sex, smoking, and spinal cord injury. Conclusion. Patients with ASD experiencing a fracture of the cervicothoracic region are at high risk of developing complications. The posterior instrumentation of cervical spinal fractures related to ASD is recommended due to biomechanical superiority. Level of Evidence: 4